HMGB1 in Pediatric COVID-19 Infection and MIS-C: A Pilot Study - Petrarca, Laura; Manganelli, Valeria; Nenna, Raffaella; Frassanito, Antonella; Ben David, Shira; Mancino, Enrica; Garofalo, Tina; Sorice, Maurizio; Misasi, Roberta; Midulla, Fabio (Frontiers in Pediatrics, 2022)
Objectives Since the beginning of coronavirus disease 2019 (COVID-19) pandemia, a novel syndrome known as Multisystem Inflammatory Syndrome in children (MIS-C) was reported in previously healthy children. A possible proinflammatory molecule, High-mobility group box 1 (HMGB1), may be assumed to play an important role in the pathogenesis and clinical presentation of MIS-C. We described the clinical picture of MIS-C patients and we also aimed to test and compare MIS-C patients HMGB1 serum levels to those of patients with previous SARS-CoV2 infection and healthy children. Study design We determined HMGB1 levels by Western Blot in 46 patients, divided into three groups: 5 patients with MIS-C (median age 8.36 years), 20 children with a history of SARS-CoV-2 infection (median age 10.45 years) and 21 healthy children (controls) (median age 4.84 years), without evidence of respiratory infection in the last 3 months. Results The median level of HMGB1 in the serum of 5 patients with MIS-C was found to be significantly higher compared both to patients with recent history of COVID-19 (1151.38 vs 545.90 densitometric units (DU), p=0.001) and control (1151.38 vs 320.33 DU, p=0.001) groups. HMGB1 level in MIS-C patients with coronary involvement had slightly higher value with respect to patients without coronary dilatation (1225.36 vs 1030.49 DU, p=0.248). In two of the five children with MIS-C that performed a follow-up, the HMGB1 value decreased to levels that were superimposable to the ones of the control group. Conclusions The significant high level of HMGB1 protein found in the serum of COVID-19 and MIS-C patients supports its involvement in inflammatory manifestations, suggesting HMGB1 as a potential biomarker and therapeutic target in patients with severe illness.